Cytometry‐based single‐cell analysis of intact epithelial signaling reveals MAPK activation divergent from TNF‐α‐induced apoptosis in vivo. Issue 10 (October 2015) - Simmons, Alan J; Banerjee, Amrita; McKinley, Eliot T; Scurrah, Cherie' R; Herring, Charles A; Gewin, Leslie S; Masuzaki, Ryota; Karp, Seth J; Franklin, Jeffrey L; Gerdes, Michael J; Irish, Jonathan M; Coffey, Robert J; et al.
Abstract: Understanding heterogeneous cellular behaviors in a complex tissue requires the evaluation of signaling networks at single‐cell resolution. However, probing signaling in epithelial tissues using cytometry‐based single‐cell analysis has been confounded by the necessity of single‐cell dissociation, where disrupting cell‐to‐cell connections inherently perturbs native cell signaling states. Here, we demonstrate a novel strategy (Disaggregation for Intracellular Signaling in Single Epithelial Cells from Tissue—DISSECT) that preserves native signaling for Cytometry Time‐of‐Flight (CyTOF) and fluorescent flow cytometry applications. A 21‐plex CyTOF analysis encompassing core signaling and cell‐identity markers was performed on the small intestinal epithelium after systemic tumor necrosis factor‐alpha (TNF‐α) stimulation. Unsupervised and supervised analyses robustly selected signaling features that identify a unique subset of epithelial cells that are sensitized to TNF‐α‐induced apoptosis in the seemingly homogeneous enterocyte population. Specifically, p‐ERK and apoptosis are divergently regulated in neighboring enterocytes within the epithelium, suggesting a mechanism of contact‐dependent survival. Our novel single‐cell approach can broadly be applied, using both CyTOF and multi‐parameter flow cytometry, for investigating normal and diseased cell states in a wide range of epithelial tissues. Synopsis: "DISSECT", a novel approach for cytometry‐based single‐cell analysis of epithelial signaling, reveals divergent regulation of p‐ERK and apoptosis and indicates a "bystander" survival program during TNF‐α‐induced apoptosis of the in vivo intestinal epithelium. A novel method, DISSECT, generates single‐cell suspensions that preserve native cell morphology, cell surface markers and intact in vivo signaling when rigorously compared to bulk approaches. DISSECT coupled to multiplex cytometry robustly characterizes the functional state of individual epithelial cells and can generate cell type‐ or "single cell"‐specific biological insights. TNF‐α induces apoptosis almost exclusively in enterocytes and not in other epithelial cell types. Single‐cell signaling analysis identifies a non‐cell autonomous, p‐ERK‐dependent survival program in the direct neighbors of the dying cell. This may represent a mechanism for preventing contiguous barrier defects in an intact epithelium. Abstract : "DISSECT", a novel approach for cytometry‐based single‐cell analysis of epithelial signaling, reveals divergent regulation of p‐ERK and apoptosis and indicates a "bystander" survival program during TNF‐α‐induced apoptosis of the in vivo intestinal epithelium.